ANALISIS KETIDAKPUASAN NASABAH TERHADAP ATM BANK PERMATA TBK - Stanty Aufia Rachmat (Jurnal Ilmiah Ekonomi Bisnis, 2015)
PT Bank Permata Tbk is one of the bank is very well known in Indonesian society. As a result of sharp competition among banks in Indonesia, making the bank owners should be observant in regard customer desires. Including PT Bank Permata Tbk should be able to provide extra services both in terms of service and in terms of products. By knowing the exact wishes of customers can help companies to improve the quality and image of the company. ATM is one of the products offered by Bank Permata. This study aims to see a relationship between the variables that have been presented by researchers with the level of consumer dissatisfaction. Samples in this study as many as 100 people. The results of trials that have been conducted, most consumers, especially Permata Bank ATM is not enough to feel satisfied with the services provided. ATM Permata have functions pretty much in demand by the public, because it is expected to ATM Permata able to give satisfaction. But sometimes the ATM also has a problem that can make the customer disappointed and dissatisfied. A constraint that often arises is the lack of the number of ATMs, the old damage repaired, less spread of ATMs in public places and so on. This is what must be addressed by Bank Permata, because the increasing number of business banking spread in Jakarta in particular. Keywords: dissatisfaction, customer, atm, permata bank